TurgoLab - Heymans, Adrien (SciLifeLab Serve, 2026)
TurgoLab is an interactive, FEM-based simulation app for inflating 2D cellular structures from .geo files. It integrates the BVPy framework to enable intuitive biomechanical modeling of plant tissues under turgor pressure from the geometry made with Anatomeshr .